ENHANCED SPEED AND ACCURACY IN COCOA FRUIT DISEASE IDENTIFICATION USING THE INCEPTION-RESNET CONVOLUTIONAL NEURAL NETWORK (CNN) ALGORITHM - Iskandar, Dadang; Novanto, Adi; Kurniawan, Yogiek Indra (Jurnal Teknik Informatika (Jutif), 2025)
The increase in world cocoa consumption is not accompanied by an increase in production, causing a problem of supply shortages in the world. One of the causes of the stagnation in the increase in cocoa production is due to diseases that attack cocoa fruit. The disease can cause unproductive plants, unusable cocoa fruit, and even cause the spread of epidemics in a cocoa fruit garden. One of the preventions that can be done is to identify diseases in cocoa fruit in order to reduce the spread of the disease. The identification process is usually carried out independently by farmers. Identification of cocoa fruit diseases requires knowledge and experience by farmers, so it can cause misidentification or failure to identify the disease. In addition, other factors can arise such as the number of farmers who check, the area of ​​the cocoa fruit garden, and the urgency of identification. To help overcome these problems, a Convolutional Neural Network (CNN) model was developed with the Inception and ResNet architectures. The data used were images obtained from Davao City, Philippines. The model obtained from the analyzed dataset got the best results of 0.99, a specificity value of 0.99, and an F1-score value of 0.99. The model configuration used is a learning rate value of 0.0001, RMSProp optimization function, initialization function (x) He uniform, initialization function (y) Glorot normal, and a batch size of 32.